Catheter ablation in patients with ventricular fibrillation by purkinje de-networking - Sciacca, Vanessa; Fink, Thomas; Guckel, Denise; El Hamriti, Mustapha; Khalaph, Moneeb; Braun, Martin; Sohns, Christian; Sommer, Philipp; Imnadze, Guram (Frontiers in Cardiovascular Medicine, 2022)
Ventricular fibrillation (VF) is a leading cause of cardiovascular death worldwide. However, arrhythmia recurrence rates are high leading to mortality and morbidity. Recently, Purkinje fibers have been identified as potential sources of VF initiation and maintenance. The study analyzes feasibility and effectiveness of catheter ablation in patients with recurrent VF by specific Purkinje de-networking (PDN). Consecutive patients with recurrent VF undergoing PDN were included into this observational study. The procedural endpoint was non-inducibility of sustained ventricular arrhythmia. 3D-anatomical mapping was conducted and the specific cardiac conduction system and Purkinje fibers were tagged. All detectable Purkinje signals were ablated in the left ventricle (LV). Additional right ventricular (RV) PDN was performed in case of VF inducibility after LV ablation. Follow-up was performed by patient visits at our outpatient clinic including device interrogation and by telephone interviews. Eight patients were included into the study. Six patients were females (75 %), mean age at procedure was 46±13.8 years and mean body mass index was 26.9±6.6 kg/m². Four patients (50%) had a known structural heart disease with two cases of ischemic cardiomyopathy and two cases of dilated cardiomyopathy. In four patients (50%) no underlying structural heart disease could be identified. Median left ventricular ejection fraction was 42±16.4 %. All patients had an ICD prior to ablation with documentation of recurrent VF. Mean number of ICD-shocks before ablation was 6±4.5. Left ventricular PDN was performed in all patients. In two patients (25%) additional right ventricular PDN was performed. Non-inducibility of any ventricular arrhythmia was achieved in all patients after PDN. Two patients showed complete left bundle branch block post ablation. Mean follow-up duration was 277±100 days. Two patients (25%) experienced ventricular arrhythmia recurrence with recurrent ICD-shock delivery. One patient died during follow-up with an unknown cause of death. Six patients (75%) experienced no arrhythmia recurrence during follow up. PDN represents a novel treatment option for patients with recurrent VF without arrhythmia substrate or specific arrhythmia triggers with promising results in terms of efficiency and feasibility. Larger and prospective studies are needed for systematic evaluation.